2007
DOI: 10.1007/s00221-007-0882-7
|View full text |Cite
|
Sign up to set email alerts
|

Postural control anomalies in children with Tourette syndrome

Abstract: The goal of the present study was to determine whether postural control is aVected in Gilles-de-la-Tourette syndrome (TS). Center of pressure (COP) displacements were recorded in children with TS and unaVected siblings in three conditions using a force platform: (1) Eyes-Open, (2) Eyes-Closed, (3) One-Leg standing with eyes open. The COP range and velocity were higher in children with TS than in unaVected siblings in all conditions. These diVerences could not be attributed to age, present tic severity, comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Children with TS showed a higher sway velocity than controls confirming previous results [11]. This effect is independent of tic severity or behavioural comorbidities in this population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Children with TS showed a higher sway velocity than controls confirming previous results [11]. This effect is independent of tic severity or behavioural comorbidities in this population.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, we reported the presence of sub-clinical postural control anomalies in children with TS [11]. Larger and faster deviations of the center of pressure (COP) were observed in these patients compared to unaffected siblings and these anomalies appear to be independent of TS severity or comorbidities.…”
Section: Introductionmentioning
confidence: 95%
“…This would explain why in some studies no poor balance performance was found in children with ADHD. For example, in a recent study involving children with Tourette syndrome, 106 ADHD symptoms had no influence on postural balance. Nevertheless, poor balance control in ADHD may also be caused by cerebellar abnormalities 16,66 .…”
Section: Discussionmentioning
confidence: 94%
“…This is well in line with our finding of increased WMV in the sensorimotor cortex, and is in good agreement with the concept of an involvement of somatosensory pathways in TS. Apart from a recent structural MRI study which demonstrated thinning of the sensorimotor cortex in children with TS [ 44 ], behavioural and neurophysiological studies provide further evidence for abnormal sensory-motor processing in TS patients [ 45 , 46 ]. These structural alterations may represent an adaptive response of the somatosensory system to abnormal input from fronto-striatal circuits.…”
Section: Discussionmentioning
confidence: 99%